Descriptive Study of STANDARD SHOPPING ANALYSIS (Technical Assistance and Training) NORTH MAMUJU REGENCY - Amir, Andi Mattulada (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2018)
The preparation of the Shopping Expenditure Analysis (ASB) aims to serve as a guideline for the North Mamuju Local Government in drafting the Work Plan and Regional Work Unit Budget (RKA - SKPD) documents and establishing specific regional revenue and expenditure budgets for Assistance and Technical Training activities. This ASB model can be used SKPD in calculating the total ideal budget for each type of activity as well as its distribution into each shopping item. In formulating our ASB models based on the Budget Implementation Document (DPA) data of all SKPD within the Government of North Mamuju Regency. The DPA data used as the basis covers the previous budget DPA. This is with consideration that the budget contained in the DPA has been run by each SKPD. The ASB models obtained are the result of equalizing the activities that appear in the DPA document. So it can be effectively used in determining budgets for pre-existing or uniform types of activities. The emergence of new types of activities, or those that can not be synchronized with existing models, requires that changes in this ASB document be made.